Imagining the Kibbutz : Visions of Utopia in Literature and Film - Omer-Sherman, Ranen (Book collections on Project MUSE., 2015)
"An exploration of the literary and cinematic representations of the kibbutz movement in Israel. Authors discussed include Amos Oz, Savyon Liebrecht, Nathan Shaham, Avraham Balaban, Atallah Mansour, Eli Amir, and Batya Gur. Directors discussed include Yitzhak Yeshurun, Akiva Tevet, Dror Shaul, and Jonathan Paz"--Provided by publisher